The Neuroprotective Agent CNTF Decreases Neuronal Metabolites in the Rat Striatum: An in Vivo Multimodal Magnetic Resonance Imaging Study. Issue 6 (June 2015) - Sauvage, Maria-Angeles Carrillo-de; Flament, Julien; Bramoulle, Yann; Haim, Lucile Ben; Guillermier, Martine; Berniard, Aurélie; Aurégan, Gwennaëlle; Houitte, Diane; Brouillet, Emmanuel; Bonvento, Gilles; Hantraye, Philippe; Valette, Julien; et al.
Ciliary neurotrophic factor (CNTF) is neuroprotective against multiple pathologic conditions including metabolic impairment, but the mechanisms are still unclear. To delineate CNTF effects on brain energy homeostasis, we performed a multimodal imaging study, combining in vivo proton magnetic resonance spectroscopy, high-performance liquid chromatography analysis, and in situ glutamate imaging by chemical exchange saturation transfer. Unexpectedly, we found that CNTF expression through lentiviral gene transfer in the rat striatum significantly decreased the levels of neuronal metabolites ( N -acetyl-aspartate, N -acetyl-aspartyl-glutamate, and glutamate). This preclinical study shows that CNTF remodels brain metabolism, and suggests that decreased levels of neuronal metabolites may occur in the absence of neuronal dysfunction.